INDEKS REPRODUKSI KAMBING PADA SISTEM PENGELOLAAN BERKELOMPOK DAN INDIVIDUAL DI PEDESAAN(DOE REPRODUCTION INDEX UNDER ORGANIZED AND INDIVIDUAL MANAGEMENT SYSTEM IN RURAL AREAS) - Sodiq, Akhmad (Pembangunan Pedesaan, 2001)
A study focusing on doe reproduction index under organized and individual management system in rural area, had been carried out in Lumbir Subdistrict Banyumas Regency The research was aimed at determining the level of doe reproduction index under organized and individual and individual management system and examining the effect of those systems A total of 48 Peranakan Etawah does were involved in this study by on-farm research. The variables studied consisted of litter size, preweaning survival rate kidding interval, doe reproduction index, and management practice. Data were analy. zedbiy descriptive and compare means supported by package of the Statistic at Product and Service Solution ( Norusis.1993). The results-showed- that (l) trhe level of doe reproduction index under organized managemen system and individual mananagemens system were 2.23 and 1.89 head / doe / year, respectively,( 2) under organized management system appears doe reproduction index was higher than at individual management system, (3) thep rimary factors of the overhanging doe reproduction index under individual management system were threateninogn kiOi survival, supported by longer in kidding interval and low litter size.